PERAN PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID) KOTA SEMARANG DALAM MEWUJUDKAN KETERBUKAAN INFORMASI PUBLIK (Studi Implementasi Undang-Undang Nomor 14 Tahun 2008) - Andhika Dwi Nugroho; Pudji Astuti (Journal of Politic and Government Studies, 2019)
The right to obtain information is a human right and public information disclosure is one of the important characteristics of a democratic country that upholds the sovereignty of the people to realize a good state administration. Openness of information is a means of optimizing public supervision of state administration and other public bodies and everything that results in public interest as mandated in Law No. 14 of 2008. The research methods used in writing this essay are qualitative research methods. The data source in this study uses primary data and secondary data. The data collection techniques used were document studies, and direct interviews. The results showed that the role of the Information and Documentation Management Officer (PPID) in realizing public information disclosure in Semarang City was in accordance with Law Number 14 of 2008. Nevertheless problems were still found in the process of implementation, both technical and general constraints themselves. Suggestions from the results of this study are to add staff / human resources in the field of IT, Add a separate room for activity and data storage for Assistant PPID. and create a data bank that has been validated by OPD officials in charge so that information can be presented at all times. In addition, the Semarang City PPID is expected to provide technical guidance for Assistant PPID, given the slow distribution of information in each field of service as the Assistant PPIDKeywords : Openness, Public Information, PPID, Semarang City